Oral Symptoms and Oral Health-Related Quality of Life among Malaysian Patients with Diabetes Mellitus - Noraini Mohamad; Goh Pin Hui; Wan Muhamad Amir Wan Ahmad; Zainab Mat Yudin (Association of Support to Oral Health Research (APESB), 2024)
Objective: To determine the association between oral health-related symptoms and oral health-related quality of life (OHRQoL) among diabetic patients. Material and Methods: This cross-sectional study involved 202 diabetic patients. The Malay version of the Short Oral Health Impact Profile [S-OHIP(M)] questionnaire was used to assess OHRQoL. A higher S-OHIP(M) score indicates greater oral impact and worse OHRQoL. The prevalence of oral impact was determined by the percentage of participants who reported experiencing one or more impacts 'very often' or 'fairly often'. An additional self-administered questionnaire was used to obtain perceived oral health symptoms. Data were analyzed using descriptive analysis, independent t-test, and ANOVA. Results: 45.6% of respondents reported at least one oral health symptom. The most common symptoms were bad breath (30.2%), cavities (29.7%), and toothache (16.8%). The prevalence of oral impact was 33.7%, and the total mean S-OHIP(M) score was 6.15 (SD=6.09). The mean of the S-OHIP(M) score was significantly higher in participants with toothache, cavities, sore gums, swollen gums, bleeding gums, mobile teeth, and bad breath. Conclusion: Oral health symptoms are significantly associated with poorer OHRQoL among diabetic patients. Preventive care and timely treatment of oral health issues are critical to improving the overall quality of life and well-being of this population.